Toward a systematic approach to assessment and care planning in palliative care: A practical review of clinical tools. Issue 2 (11th June 2015) - Hudson, Peter; Collins, Anna; Bostanci, Adam; Willenberg, Lisa; Stephanov, Nikola; Phillip, Jennifer
ABSTRACT: Objective: Ensuring a consistent and systematic approach to the delivery of care for people with advanced disease is a priority for palliative care services worldwide. Many clinical tools are available to aid in this process; however, they are often used sporadically, and implementation of a routine set of clinical tools to guide care planning in the specialist palliative care sector in Australia has not been achieved. This study sought to recommend key clinical tools that may assist with the assessment and care planning of specialist palliative care provision for patients and family caregivers admitted to specialist palliative care settings (home, hospital, and hospice). Method: A mixed-methods sequential approach over four phases was employed, involving: (1) a palliative care sector survey, (2) a systematic literature review, (3) an appraisal of identified clinical tools, and (4) a focus group with an expert panel who critiqued and endorsed a final suite of clinical tools recommended for specialist palliative care. Results: Twelve tools with practical relevance were recommended for use across settings of care. Significance of Results: Palliative services should review current practices and seek to implement this recommended suite of tools to enhance assessment and guide care delivery across care settings. Subsequent evaluation should also occur.